Muslim women and Islamic family law : lived experiences in Britain - Uddin, Islam, 1971- (Routledge, 2025)
"This book investigates the practice of Islamic family law among Muslim women in a minority context. Muslims living as a minority often practise Islamic family law in a private capacity, following customary laws from their countries of origin. The invocation and operation of law in this context is, however, understudied and little understood. In response, this book provides an empirical study of the practice of Islamic family law in Britain. The book analyses the lived experiences of Muslim women and their interactions with the processes of marriage and divorce. Focusing centrally on Muslim women's agency and legal consciousness, the book is based on in-depth interviews with Muslim women and with relevant professionals, as well as observations of Shariah council hearings and the analysis of related documentation. The book thus offers a rich and nuanced account of how Muslim women currently navigate marriage, marital discord, dispute resolution, divorce and post-divorce, offering insights that will better facilitate just outcomes for them. This book will be of interest to scholars, students and researchers in the fields of Islamic family law in minority contexts, as well as legal practitioners, policymakers and community activists working in this area"--